(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The tessera from Herrera de Pisuerga (Palencia) records the religious sanction of the pacts established at the end of the Augustan Principate between two Indo-european peoples in Hispania. According to the available evidence and parallels, the rituals concerned would be performed in the frontier of the territory of the ciuitas Maggauiensium when Amparamus of Cusabura and his family were granted the honorary citizenship of that city.